Idiopathic pulmonary fibrosis: prime time for a precision-based approach to treatment with N-acetylcysteine. Issue 1 (5th January 2021) - Podolanczuk, Anna J.; Noth, Imre; Raghu, Ganesh
Oxidative stress, the total sum of molecular and cellular processes that result from excess oxidant production and antioxidant depletion, has long been implicated in the pathogenesis of idiopathic pulmonary fibrosis (IPF) [1, 2]. Bronchoalveolar lavage fluid from patients with IPF exhibits enhanced oxidative activity, and high levels of the oxidants hydrogen peroxide, superoxide and hydroxyl radicals induce injury to alveolar epithelial cells [3]. At the same time, glutathione levels are depleted in the lower respiratory tract of IPF patients compared to healthy subjects and correlate with disease severity [4, 5]. Excess production of reactive oxygen species in IPF occurs in activated inflammatory and alveolar epithelial cells through induction of NADPH oxidase, endoplasmic reticulum stress and uncoupling of the mitochondrial electron transport chain [2]. Exogenous oxidants from cigarette smoke, occupational exposure, air pollution and others further augment the oxidant burden in the lungs of people genetically predisposed to IPF [1]. Increased oxidative stress leads to DNA damage, alveolar epithelial cell apoptosis, release of pro-fibrotic cytokines and activation of matrix metalloproteinases, promoting myofibroblast proliferation and extracellular matrix remodelling (figure 1). Transforming growth factor β inhibits glutathione synthesis in a positive feedback loop, leading to ongoing cellular damage. Prime time for a precision-based approach for treatment of idiopathic pulmonary fibrosis with an antioxidant, N -acetylcysteine https://bit.ly/30gl9vG